Standardization of reconstructions with flaps after Fournier’s gangrene - Rui Lopes; Lucas Carvalho Lopes (Revista Brasileira de Cirurgia Plástica)
Introduction: Fournier’s gangrene is characterized by tissue necrosis, which requires treatment employing debridement and antibiotics with wounds of varying sizes. The objective is to standardize the surgical techniques of reconstructions with flaps used to treat wounds after Fournier’s gangrene. Method: A study was conducted by searching the PubMed/Medline, SciELO, and LILACS databases. Results: In wounds with skin loss of 25% to 50%, a local advancement cutaneous flap or a pudendal flap from the thigh was used; in wounds, greater than 50%, a superomedial thigh flap or myocutaneous flap from the gracilis muscle was used, with the aim of to enable proper reconstruction. Conclusion: Advancement and pudendal thigh flaps were used for wounds with up to 50% loss of scrotal skin substance, while the myocutaneous gracilis flap and supero-medial flap of the thigh were indicated for wounds with more than 50% of the total scrotal surface affected, after Fournier gangrene.